PAI Teacher Strategy in Instilling Religious Attitudes in Class VII Students at Gema Buwana Private Middle School - Anisa Oktaviana; Arlina, Arlina; Jeesica Shinta; Chairunnisa Sahril Chaniago; Fery Fadli (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to determine PAI teachers' strategies for instilling religious attitudes in class VII students at Gema Buwana Private Middle School. The focus of the study is on three things, namely what strategies are used by teachers in instilling religious attitudes in class VII at Gema Buwana Private Middle School, what PAI teachers' strategies are in instilling religious attitudes in class VII at Gema Buwana Private Middle School, and the reasons why PAI teacher strategies are needed in instilling a religious attitude in class VII of Gema Buwana Private Middle School. The research method used is qualitative based on descriptive studies. The data collection techniques used were observation, interviews and documentation studies. The data obtained was then analyzed using the Miles and Huberman technique, namely data reduction, data presentation, and drawing conclusions. The research results explain that teachers are called PAI teachers because their main task lies in the ability to teach how the Islamic religion can be understood and implemented by students appropriately and proportionally. The process of knowing, understanding and applying is not as easy as turning the palm of your hand. It needs a mature, long, continuous or systematic process. Therefore, there needs to be a conscious process to develop all human potential so that Islam can function as a solution to solve the problems of people's lives.